2022
DOI: 10.3390/buildings12101493
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Models for Predicting Shear Strength and Identifying Failure Modes of Rectangular RC Columns

Abstract: The determination of shear strength and the identification of potential failure modes are the crucial steps in designing and evaluating the structural performance of reinforced concrete (RC) columns. However, the current design codes and guidelines do not clearly provide a detailed procedure for governing failure types of RC columns. This study predicted the shear strength and identified the failure modes of rectangular RC columns using various Machine Learning (ML) models. Six ML models, including Multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Congregating numerical and experimental results, they concluded that the collapse likelihood of a substandard RC under design earthquake increases from 4.20% to 29.20%. Phan et al [10] integrated regression and classification schemes to predict shear strength and failure modes in rectangular RC columns. Using 541 experimental datasets, they concluded that the K-nearest neighbor (KNN) outperformed any other classifier or regressor.…”
Section: Seismic Impact On Buildings: a Bird's Eye Viewmentioning
confidence: 99%
“…Congregating numerical and experimental results, they concluded that the collapse likelihood of a substandard RC under design earthquake increases from 4.20% to 29.20%. Phan et al [10] integrated regression and classification schemes to predict shear strength and failure modes in rectangular RC columns. Using 541 experimental datasets, they concluded that the K-nearest neighbor (KNN) outperformed any other classifier or regressor.…”
Section: Seismic Impact On Buildings: a Bird's Eye Viewmentioning
confidence: 99%
“…ML is widely used in a variety of fields from everyday applications like image recognition [16] to engineering applications such as microstructural characterization and prediction of mechanical response of crystalline materials [17,18]. Furthermore, ML has been used for failure mode identification and strength prediction in columns [19][20][21][22].…”
Section: Machine Learning Modelmentioning
confidence: 99%
“…Recently, several studies have applied ML techniques to recognize the FMs and predict the capacity of RC columns with solid sections, of which typical works include Mangalathu and Jeon [41], Feng et al [6], Mangalathu et al [39], and Phan et al [42]. Although previous ML models showed good promise, they are still unclear on optimizing hyperparameters effectively.…”
Section: Introductionmentioning
confidence: 99%